The Penerapan Puzzle-Based Learning untuk Mengajar Sains di Pasantren dengan Kelas Heterogen - Ogi Danika Pranata (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
The main problem face by teachers in heterogeneous classes is how to choose and teach subjects properly. The subject may too difficult for a low level students (Elementary School) or too easy for a high level students (Secondary School). Puzzle-based learning applied as an alternative solution for teaching in heterogeneous classes in plane geometry topics. Puzzle-based learning can create interesting learning situations for low levels students and not boring for higher levels students. Furthermore, puzzle-based learning can also increase motivation, activity, argument, and conceptual understanding. The understanding of subject indicated by the student's score after attending the lesson with a high average, which is 80.17. In the end, the teacher found that most of the students viewed puzzle-based learning as useful for learning, especially in mathematics and science.